Relationships between motion of the shoulder joint and the maximal height of vaulters' centre of gravity - Kageyuki, T.; Matsubayashi, T.; Ohyama-Byun, K.; Kigoshi, K. (ISBS Proceedings Archive (Michigan), 2019)
The purpose of this study was to clarify the effect of the shoulder joint motion during vaulting on the maximal height of vaulters` centre of gravity (CGv). Eight male vaulters (personal best record: 4 m 60 to 5 m 77) vaulted over a cross bar with run-ups and pole in the same set up as competitions. Three-dimensional coordinates of the body were collected using a motion capture system (250 Hz). The angular displacement of the shoulder joint on the lower grip side between take-off and swing and on the upper grip side between rock back and pole straight showed high correlations with the maximal height of the CGv (r = 0.78 and -0.91, respectively). These results suggest that the shoulder joint motions because this motion could make it easy for vaulters and poles to rotate around the lower tip and possible for them to receive the recoil force of the poles effectively.